Ushuni as a method of sound production, performance practice and categorisation in the philosophical and intellectual foundation of Umaskandi - Moloi, Mbuti; Mapaya, Geoff (Research Journal in Advanced Humanities, 2022)
The focus of this article is to demonstrate and explain how employing linguistic apparatus, the epistemological and metaphysical world of omaskandi can be explored and understood. It does so by focusing on ushuni as the method of sound production, performance practice and categorisation method. The focus on ushuni demonstrates that the indigenous African languages Isizulu in particular, which plays a significant role as it dominates the conceptual apparatus beyond its ordinary communicative function, ought to be fundamental in rationalising and theorising about umaskandi. Isizulu language, therefore, should accordingly enable and guarantee access to umaskandi’s profound conceptual levels. The study has assumed the qualitative research paradigm as it offers an in-depth analysis of reality. Primarily, the investigation into the nature of umaskandi was conducted through fieldwork, and equally important was the consideration of the known history of the genre through earlier documentation. This article, therefore, attempts to unpack Isizulu indigenous music-making principles, practices, and contexts in which umaskandi exists. It is envisaged that it will be more beneficial to umaskandi genre, omaskandi and formal music education hence contributing to knowledge production about this musical phenomenon.